A Rarely Seen Case: Congenital Cystic Adenomatoıd Malformation, Type 0 - Gürbüz, Emre; Atan, Yusuf; Akçay, Arzu (The Bulletin of Legal Medicine, 2022)
Congenital cystic adenomatoid malformation is a hamartomatous lung anomaly. It constitutes 25% of all congenital lung anomalies and divides 5 subtypes. It is aimed to increase the variety of Type 0 in the literature which is very rare type. A term baby girl at 40th weeks of gestation, from a 19-year-old mother was delivered. The APGAR score of baby was determined 1-1 and baby was intubated. Detection of left sided pneumothorax a chest tube placed. But the baby could not survive after resuscitation period. After the histopathological examination of the lungs it was diagnosed as Cystic Adenomatoid Malformation Type 0 (bilateral diffuse). By the presented case, this pathology is described with all its detectable aspects, the anomalies that may accompany, how the histopathological samples should be taken. It is intended to be shared with Forensic Medicine Specialists, Pathologists and Pediatrics Specialists.
Keywords: congenital cystic adenomatoid malformation; type 0; autopsy; pathology; forensic medicine